A short history of global evangelicalism - Hutchinson, Mark, 1958-; Wolffe, John. (Cambridge [England] ; New York : Cambridge University Press, 2012)
"This book offers an authoritative overview of the history of evangelicalism as a global movement, from its origins in Europe and North America in the first half of the eighteenth century to its present-day dynamic growth in Africa, Asia, Latin America, and Oceania. Starting with a definition of the movement within the context of the history of Protestantism, it follows the history of evangelicalism from its early North Atlantic revivals to the great expansion in the Victorian era, through to its fracturing and reorientation in response to the stresses of modernity and total war in the late nineteenth and early twentieth centuries. It describes the movement's indigenization and expansion toward becoming a multicentered and diverse movement at home in the non-Western world that nevertheless retains continuity with its historic roots. The book concludes with an analysis of contemporary worldwide evangelicalism's current trajectory and the movement's adaptability to changing historical and geographical circumstances"--
"In October 1757, Thomas Haweis, a young Cornishman, was ordained to the curacy of St Mary Magdalen church in Oxford. Haweis's ministry rapidly stirred strong reactions. According to Charles Wesley, a co-founder of Methodism, he preached 'Christ crucified, with amazing success,' and drew large crowds both from the University and the city. On the other hand, students jeered Haweis in the street, shouting 'There goes the saver of souls!': stones were thrown through the church windows while he was preaching, and 'This is the back way to Hell' was chalked on the church doors. More orderly, but ultimately more effective, critics eventually forced Haweis to leave Oxford in 1762. Not to be repressed, Haweis subsequently published a selection of the sermons he had delivered in Oxford under the overall title of Evangelical Principles and Practice. It was one of earliest attempts systematically to set out the theological outlook of the developing evangelical movement and its implications for Christian devotion and practice. Haweis's starting point was 'The Divinity of the SON and SPIRIT, co-eternal and co-equal with the FATHER'. He affirmed 'the inability of man in his fallen state to do any thing but evil' and the impossibility of human compliance with God's Law"--
1. Understanding evangelicalism -- 2. 'The surprising work of God': origins to 1790s -- 3. Volunteering for the kingdom: 1790s to 1840s -- 4. The kingdom enlarged and contested: 1840s to 1870s -- 5. A new global spiritual unity: 1870s to 1914 -- 6. Fighting wars and engaging modernity: 1900s to 1945 -- 7. Towards global trans-denominationalism: 1945 to 1970s -- 8. 'The actual arithmetic': a survey of contemporary global evangelicalism -- 9. Localism and transnationality: 1970s to 2010 -- 10. Conclusion.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Evangelicalism -- History; RELIGION / History; RELIGION / Christianity / Pentecostal & Charismatic; RELIGION / Fundamentalism; Electronic books